The Effectiveness of Kangaroo Mother Care (KMC) on attachment of mothers with premature infants - Shahrokh Mehrpisheh; Zahra Doorandish; Roya Farhadi; Mozhgan Ahmadi; Mannaneh Moafi; Forouzan Elyasi (Elsevier, 2022)
Objective: Attachment is a socio-emotional relationship between the mother and infant that increases the probability of a preterm infant's survival. This study aimed to evaluate the effectiveness of Kangaroo Mother Care (KMC) on maternal attachments of mothers with premature infants. Study design: This quasi-experimental study was performed on 100 mothers of premature infants who were admitted to neonatal intensive care units. A questionnaire comprising demographic information and the Maternal Attachment Scale were used as data collection tools. All data analysis was performed using SPSS software version 25. Significant level is considered P < 0.05. Results: After the intervention, the levels of maternal attachment of mothers in the intervention group were significantly higher than in the control group (47.7 ± 2.9vs. 40.4 ± 5.4, P = 0.003). After the intervention, the infants in the intervention group has a significantly higher number of breastfeeding than the control group (10.6 ± 1.8 vs. 8.2 ± 1.6, P = 0.000). Moreover, the infant of the intervention group had a statistically significant higher weight at discharge time (2164.4 ± 481.1 vs. 1965.2 ± 372, P = 0.042). Conclusion: The results of the present study showed that Kangaroo Mother Care can be used to improve the maternal attachments in mothers with premature infants. It improves the breastfeeding and weight gain status in infants as well.